Use of dirty plastic waste as precursors for activated carbon production—A contribution to the circular economy - Cansado, Isabel Pestana da Paixão; Mourão, Paulo Alexandre Mira; Nabais, João Manuel Valente; Tita, Bárbara; Batista, Teresa; Rocha, Telmo; Borges, Cátia; Matos, Gilda (Water and environment journal : WEJ, 2022)
The production of activated carbons (ACs) from dirty plastic wastes derived from the mechanical/biological treatment of urban solid wastes, disposable plastics and plastics used in agriculture is reported. The use of these precursors is innovative and contributes to the circular economy by the valorization of dirty plastics that are usually disposed in landfills. ACs were produced by physical activation, with air or CO2, and chemical activation, with KOH or K2CO3. ACs presented a BET (N2) area and pore volume up to 723 m2/g and 0.32 cm3/g. Selected samples were tested for the 2,4‐dichlorophenoxyacetic acid (MCPA) and 4‐chloro‐2‐methyl‐phenoxyacetic acid (2,4‐D) removal from the liquid phase. PB‐K2CO3‐1:1–700 presented an apparent maximum adsorption capacity of 245 and 289 mg g−1 for MCPA and 2,4‐D, respectively.